Toxicological properties of activated carbons with saturated by cationic surfactant surface - V. Sharov, Artem; M. Plotnikova, Olga; I. Rykova, Ðnna; V. Evseev, Vadim (International Journal of Engineering and Technology, 2020)
The article discusses the effects of cetyltrimethylammonium bromide, sorbed on activated carbons, on vital signs of some living systems.Extracts from carbon, saturated with cetyltrimethylammonium bromide, were injected into the organisms of laboratory mice and soil samples. The biochemical blood parameters were determined from laboratory mice. In soils was determined the enzymatic activity, as well as the number of major groups of soil microorganisms.In mice, under the influence of surfactants on active carbons, the activity of enzymes associated with the functioning of the liver changes to a greater extent. The effect on the urease activity of the soil was not detected, the phosphatase activity under the action of surfactants increases, catalase and dehydrogenase - fall. The number of oligonitrophils, oligotrophs and amylolytics is reduced. A decrease in the effect of surfactant bonded to the active carbons surface on the systems as compared with free surfactants has been recorded.The increase in the number of ammonifiers with the introduction of surfactants can be used for microbiological cleaning of waste active carbone.Â Â Â